Leveraging consumer personality and social media marketing to improve a brand's social media equity. (22nd November 2022) - Mathur, Manisha; Lawrence, Danae; Chakravarty, Anindita
Abstract: Consumer personality traits impact consumer actions, preferences, online behaviour and shopping motives. This study examines personality traits as drivers of social media equity by addressing the mechanisms under which consumer personality traits influence social media equity. We aim to combine consumer‐level information with brand‐level metrics to advance our understanding of consumers' associations with brands on social media and how specific consumer personality traits can be leveraged to improve a brand's social media equity. Using a self‐administered survey, a total of 418 respondents from an online consumer panel participated in this study. The results from structural equation modelling revealed that while extraversion, openness to experience and neuroticism personality traits are positively associated with brand engagement and brand advocacy, agreeableness and conscientiousness are significantly associated with brand advocacy and not with brand engagement. This study advances theory by examining how consumer personality traits influence social media equity via brand engagement and brand advocacy as mediators. The findings provide rich practical insights into underlying mechanisms through which marketers can increase social media equity using consumer personality traits.